2019
DOI: 10.3390/molecules24030535
|View full text |Cite
|
Sign up to set email alerts
|

Iron(III)-Catalyzed Highly Regioselective Halogenation of 8-Amidoquinolines in Water

Abstract: A simple protocol of iron(III)-catalyzed halogenation of 8-amidoquinolines in water under mild conditions was developed, affording the 5-halogenlated products in good to excellent yields up to 98%. The reaction mechanism most likely involves a single-electron transfer (SET) process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 48 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Among them, the synthesis of important C5-halogenated products gained particular attention since Stahl et al reported the first chlorination example using LiCl as the halogen source [10]. Following this pioneering work, elegant strategies for the C5-H bromination of the quinoline ring employing simple inorganic and organic bromine-containing compounds such as Br 2 , CuBr, CuBr 2 , LiBr, NaBr, KBr, HBr, NH 4 Br, and tetrabutylammonium bromide (TBAB) as halogen sources have been realized (Scheme 1, reaction 1) [11][12][13][14][15][16][17][18][19][20]. Another category of extensively used bromination reagents are brominated imides, such as N-bromosuccinimide (NBS), N-bromosaccharin (NBSA), tribromoisocyanuric acid (TBCA), 1,3-dibromo-5,5-dimethylhydantoin (DBDMH), and so on (Scheme 1, reaction 2) [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the synthesis of important C5-halogenated products gained particular attention since Stahl et al reported the first chlorination example using LiCl as the halogen source [10]. Following this pioneering work, elegant strategies for the C5-H bromination of the quinoline ring employing simple inorganic and organic bromine-containing compounds such as Br 2 , CuBr, CuBr 2 , LiBr, NaBr, KBr, HBr, NH 4 Br, and tetrabutylammonium bromide (TBAB) as halogen sources have been realized (Scheme 1, reaction 1) [11][12][13][14][15][16][17][18][19][20]. Another category of extensively used bromination reagents are brominated imides, such as N-bromosuccinimide (NBS), N-bromosaccharin (NBSA), tribromoisocyanuric acid (TBCA), 1,3-dibromo-5,5-dimethylhydantoin (DBDMH), and so on (Scheme 1, reaction 2) [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The quinoline and motified quinoline have attracted considerable attentions during the past few years due to their biological and pharmacological activities, which exist in natural products and marketed drugs (Scheme ). In the past few years, Stahl et al, Zhang et al, Huang et al, and others reported C5 chlorination of 8-aminoquinoline that is geometrically difficult to afford . However, there are some limitations and drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Stahl and coworkers first reported the remote CuCl‐catalyzed C5 chlorination of 8‐amidoquinoline amides through a single electron transfer (SET) process. Since then, regioselective C5 halogenation of quinolines has been widely investigated, and various halogen sources such as NXS (X=Cl, Br or I), halide salts, molecular idodine, and other halogen reagents have been used for the synthesis of halogenated quinolines. Despite the significant progress, most of these methods cannot avoid the use of transition‐metals, and/or excess of oxidants and halogen sources, thus not conforming to the requirements of atom economy and green chemistry.…”
Section: Introductionmentioning
confidence: 99%